2022
DOI: 10.1128/mra.00506-22
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome-Assembled Genomes of Bacterial Symbionts Associated with Insecticide-Resistant and -Susceptible Individuals of the Glassy-Winged Sharpshooter (Homalodisca vitripennis)

Abstract: The role of microbes in insecticide resistance is an emerging question. Here, we describe six metagenome-assembled genomes (MAGs) associated with the glassy-winged sharpshooter ( Homalodisca vitripennis [Germar, 1821]) (Hemiptera, Cicadellidae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, starting in 2012 the effectiveness of population control by these insecticides appeared substantially weakened ( 19 , 20 ), with documented instances of neonicotinoid applications leading to high levels of insecticide resistance in some Southern California populations resulting in GWSS population resurgence ( 21 , 22 ). Insecticide resistance usually involves multiple coexisting mechanisms spanning behavioral (e.g., avoidance) and physiological processes (e.g., cuticle modifications and detoxification) ( 23 25 ), and studies have proposed a novel role for symbionts and other associated microbes in detoxification of insecticides for their associated hosts ( 26 31 ). Recent studies on Southern California GWSS populations have identified both trade-offs in host reproductive fitness associated with resistance ( 32 ) as well as host genes that may play a role in conferring resistance ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, starting in 2012 the effectiveness of population control by these insecticides appeared substantially weakened ( 19 , 20 ), with documented instances of neonicotinoid applications leading to high levels of insecticide resistance in some Southern California populations resulting in GWSS population resurgence ( 21 , 22 ). Insecticide resistance usually involves multiple coexisting mechanisms spanning behavioral (e.g., avoidance) and physiological processes (e.g., cuticle modifications and detoxification) ( 23 25 ), and studies have proposed a novel role for symbionts and other associated microbes in detoxification of insecticides for their associated hosts ( 26 31 ). Recent studies on Southern California GWSS populations have identified both trade-offs in host reproductive fitness associated with resistance ( 32 ) as well as host genes that may play a role in conferring resistance ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, future studies should also consider whether obligate and facultative microbial symbionts of GWSS are involved in conferring insecticide resistance (e.g. [ 61 ]). We believe that this work serves as a foundation for future studies of insecticide resistance in GWSS and other Hemipteran insects.…”
Section: Discussionmentioning
confidence: 99%
“…avoidance) and physiological processes (e.g. cuticle modifications, detoxification) [23][24][25], and studies have proposed a novel role for symbionts and other associated microbes in detoxification of insecticides for their associated hosts [26][27][28][29][30][31]. Recent studies on Southern California GWSS populations have identified both trade-offs in host reproductive fitness associated with resistance [32] as well as host genes that may play a role in conferring resistance [33].…”
Section: Introductionmentioning
confidence: 99%